1987
DOI: 10.1139/v87-040
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer fluorescence of some N-benzoylindoles

Abstract: . Can. J. Chem. 65, 245 (1987). The fluorescence properties of various N-carbonyl-substituted indoles (compounds 1-7) are examined. The N-benzoyl-indole derivatives 1 and 3-5 are shown to fluoresce weakly and the effect of solvent polarity upon the energy of the emitting state and upon the quantum yield of fluorescence is described. It is concluded that the initially formed singlet excited state is non-emissive and can relax to an intramolecular charge transfer state which is weakly fluorescent. The solvent ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 5 publications
3
16
1
1
Order By: Relevance
“…It can be seen that the data point corresponding to dioxane is off the line; this has been observed in other systems [8] and may arise because the conformation of the dioxane molecule may be altered when it is solvating a charge transfer excited state. From other solvent polarisability-fluorescence wavelength correlations [8] it has been found that the effective dielectric constant of dioxane is 6 or 7.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…It can be seen that the data point corresponding to dioxane is off the line; this has been observed in other systems [8] and may arise because the conformation of the dioxane molecule may be altered when it is solvating a charge transfer excited state. From other solvent polarisability-fluorescence wavelength correlations [8] it has been found that the effective dielectric constant of dioxane is 6 or 7.…”
Section: Resultsmentioning
confidence: 65%
“…From other solvent polarisability-fluorescence wavelength correlations [8] it has been found that the effective dielectric constant of dioxane is 6 or 7. Using a value of this order brings the dioxane point onto the line in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Isoindoloindolone 1 also exhibit charge-transfer fluorescence with high quantum yields in non polar solvents. 10 …”
Section: Biological Activitymentioning
confidence: 99%
“…Los espectros de fluorescencia (λexc=325 nm) de IM y KT en disolución acuosa (datos no mostrados aquí) presentan una emisión muy débil, con máximos a 560 y 522 nm, respectivamente. La presencia de bandas a mayores longitudes de onda con un gran desplazamiento Stokes cuya posición varia con la polaridad del disolvente se debe a la existencia de un complejo de transferencia de carga también detectado en otros Nbenzoilindoles [34]. Cuando la IM está en presencia de AgNPs, su señal de fluorescencia se intensifica (efecto SEF) únicamente a pHs<4.…”
Section: B Indometacina Y Ketorolacounclassified